A Bibliometric Analysis of Entrepreneurial Thinking Research in Science Education from 2014 to 2023 - Latip, Abdul; Abdullah, Norazilawati; Kadarohman, Asep; Hernani, Hernani; Musa'adah, Siti (Jurnal Inovasi Pendidikan IPA, 2024)
This research aims to provide a bibliometric literature review regarding the trends of entrepreneurial thinking (ET) research in science education in 2014-2023. In this research, five main stages were carried out in bibliometric literature: determining topics and keywords, searching databases according to keywords, refining the database, compiling statistical data, and analyzing data. Search results from the scopus.com document database using the keywords "entrepreneurial thinking" and "science education" obtained 89 articles, which were then analyzed for completeness and statistical data. Data that have gone through the refinement stages are stored in the form of Research System Information (RIS) and analyzed using VOSviewer software to obtain visualization of the data. The results of the bibliometric review show that the entrepreneurial thinking research trend linked to science education continues to experience development with a focus on research studies on the integration of entrepreneurship in science and engineering, as well as the development of skills related to entrepreneurship through science, including entrepreneurial character, entrepreneurial intention, and entrepreneurial thinking. In more specific science education, entrepreneurial thinking has begun to be developed through STEM and design thinking since 2018. Another bibliometric review shows that research on ET still needs to be studied, especially in science teaching, which is linked to strategies, approaches, media, and teaching models. The results of the bibliometric review show that ET in science education has many opportunities for research development that can be studied further.